2021
DOI: 10.2147/jaa.s307197
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion Molecules are Upregulated and May Drive Inflammation in Chronic Rhinosinusitis with Nasal Polyposis

Abstract: Purpose Chronic rhinosinusitis with nasal polyps (CRSwNP) is predominantly characterized by eosinophil- and T helper 2 cell (Th2)-biased inflammation. Integrins and intercellular adhesion molecules (ICAMs) are superfamilies of cell adhesion molecules (CAMs) that facilitate the recruitment and trafficking of immune cells and have been implicated in coordinating eosinophil and Th2 cell adhesion and signaling in asthma. The roles of CAMs in CRSwNP, however, remain poorly understood. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…SAP-EVs overexpress ITGAM and ITGB2 that heterodimerize to form integrin αmÎČ2 [also known as macrophage-1 antigen (Mac-1)], which is implicated in intercellular migration and adhesion processes, − but ITGA2B is related to coagulation response. , Thus, to individually evaluate the effect of ITGAM and ITGB2 on lung injury, we transfected human embryonic kidney 293T (HEK293T) cells with ITGAM or ITGB2 expression vectors or an empty expression cassette (negative control vector, NCV) (Figure A) to produce EVs that specifically overexpress one of these two integrins (EV ITGAM or EV ITGB2 ) or exhibit normal integrin expression (EV NCV ). Western blot analysis confirmed ITGAM or ITGB2 overexpression in the corresponding recombinant HEK293T cells and EV isolates versus cells transfected with negative control vector and their EVs (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…SAP-EVs overexpress ITGAM and ITGB2 that heterodimerize to form integrin αmÎČ2 [also known as macrophage-1 antigen (Mac-1)], which is implicated in intercellular migration and adhesion processes, − but ITGA2B is related to coagulation response. , Thus, to individually evaluate the effect of ITGAM and ITGB2 on lung injury, we transfected human embryonic kidney 293T (HEK293T) cells with ITGAM or ITGB2 expression vectors or an empty expression cassette (negative control vector, NCV) (Figure A) to produce EVs that specifically overexpress one of these two integrins (EV ITGAM or EV ITGB2 ) or exhibit normal integrin expression (EV NCV ). Western blot analysis confirmed ITGAM or ITGB2 overexpression in the corresponding recombinant HEK293T cells and EV isolates versus cells transfected with negative control vector and their EVs (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…ITGB2 is a subunit of integrins extensively expressed in leukocytes which could conduct the extracellular signals and modulate cell responses such as cell adhesion, proliferation and differentiation ( 63 ). A recent study showed that ITGB2 was up-regulated in CRSwNP and might serve as an inflammatory mediator ( 64 ). TYROBP is a transmembrane polypeptide that regulate signal transduction in dendritic cells, macrophages and microglia.…”
Section: Discussionmentioning
confidence: 99%
“…From a bioinformatics analysis, ITGAM and ITGB2 were also up-regulated in myeloma and involved in cytokine-cytokine receptor interaction, innate immune response and inflammatory response that were similar to our results [ 40 ]. Moreover, the integrin ITGAM/ITGB2, associated with immunity and inflammation [ 41 , 42 ], was gradually increased along with hematopoietic stem cells (HSC) differentiation in mice [ 41 ], suggesting the indirect role of STK10 in immune and defense. However, this view still needs to be verified by further studies.…”
Section: Discussionmentioning
confidence: 99%